Critical Discourse Analysis: Papuan Rejection of the Free Nutritious Food Policy - Iwan Joko Prasetyo; Nur'annafi Farni Syam Maella; Nevrettia Christantyawati; Didik Sugeng Widiarto (Communicatus: Jurnal Ilmu komunikasi, 2025)
This research analyzes the media discourse construction regarding the rejection of the free nutritious meal program (MBG) policy by Papuan students through the Critical Discourse Analysis (CDA) approach using Teun A. Van Dijk's social cognition model. The focus of the research is directed toward a news article from Tempo.co titled "Thousands of Students in Papua Pegunungan Protest against Free Nutritious Meals" published on February 17, 2025. It aims to analyze the text structure, social cognition, and social context in the Tempo.co news coverage regarding the rejection of the free nutritious meal policy by Papuan students. This research uses a qualitative method with a critical discourse analysis approach developed by Teun A. Van Dijk, often known as the social cognition model. The research results show that Tempo.co's reporting not only describes the demonstrations but also reproduces the power relations between the central government and the Papuan people. At the textual level, the news places the legitimacy of the MBG policy as the main framework before presenting the reasons for rejection, while security-themed lexical choices, such as "preventing riots," "dispersing crowds," and "tear gas," frame the students' actions as a threat to public order. At the level of social cognition, it is evident that journalists prioritize official sources and policy explanations, resulting in limited space for students' structural reasons regarding educational and health disparities. At the level of social context, the construction of news discourse is closely related to the political dynamics of Papua and the tendency of national media to adopt a central perspective. The integration of the three levels of analysis reveals that media representation tends to affirm state hegemony, marginalize local voices, and normalize the actions of the authorities as part of restoring order.